Genomic and Phenomic Research in the 21st Century. Issue 1 (January 2019) - Hebbring, Scott
Abstract : The field of human genomics has changed dramatically over time. Initial genomic studies were predominantly restricted to rare disorders in small families. Over the past decade, researchers changed course from family-based studies and instead focused on common diseases and traits in populations of unrelated individuals. With further advancements in biobanking, computer science, electronic health record (EHR) data, and more affordable high-throughput genomics, we are experiencing a new paradigm in human genomic research. Rapidly changing technologies and resources now make it possible to study thousands of diseases simultaneously at the genomic level. This review will focus on these advancements as scientists begin to incorporate phenome-wide strategies in human genomic research to understand the etiology of human diseases and develop new drugs to treat them. Highlights: Human genetic research has morphed from studying rare disorders in families to common conditions in populations of unrelated individuals. Advances in biobanking, computer science, and EHRs linked to real-life clinical data have allowed for the study of thousands of diseases simultaneously via phenome-wide association studies. As genomic studies continue to grow in size and scale, both rare and common diseases may be studied simultaneously at the genome-wide and phenome-wide level, which may help understand the genetic causes of human diseases and ways to treat them.